Political Parties and Election Financingin Nigeria:Interrogating the Real Issues in the 2015 General Elections (Global Journal of Human-Social Science, 2016)
Political Parties have come to play significant roles in most democratic countries For instances they have become critical links between the State and Civil Society CSO between institutions of government and interests groups that operate within the society Other functions of political parties include i Representation ii Educating and enlightening the electorates iii Socialization mobilization and formation of government iv Goal formation v Elite formation and recruitment vi Interest formation